Brain structure and ultrastructure of gonadotropic cell in female grunting toadfish, Allenbatrachus grunniens (Linnaeus 1758) - Mitparian, Tappadit; Kettratad, Jes; Kangwanrangsan, Niwat; Ampawong, Sumate; Kaneko, Gen; Iida, Atsuo; Senarat, Sinlapachai; Charoenphon, Natthawut (Agriculture and Natural Resources, 2023)
Importance of the work: There is little known of the neurobiology of Allenbatrachus grunniens (Linnaeus 1758), an estuarine toadfish inhabiting mangrove areas of the Indo-West Pacific, including Thailand. Objectives: To identify the histomorphology of the brain and ultrastructure of the gonadotropic cells (GTH cells) in A. grunniens. Materials & Methods: Mature female fish were collected from the Pranburi River estuary. Whole brains were dissected to examine their anatomical characteristics; the ultrastructure of the GTH cells was established. Results: The large telencephalic regions and medium cerebellum likely aid in the survival of the species in structurally complex estuarine habitats. Histologically, two sub-regions of the telencephalon were similarly structured and composed of neuroglia, neurons and blood vessels. The optic lobe of the mesencephalon had six histologically distinct layers. GTH cells were identified in the adrenohypophysis of the pituitary gland. Based on electron micrography, the GTH II cells had an oval, eccentric nucleus, while the GTH I cell had a large, central nucleus and secretory granules. The secretory granules in the active GTH II cells indicated that synthetic activity might be related to final oocyte growth and ovulation. Main finding: Basic knowledge about the neurobiology of A. grunniens was revealed based on histomorphological examination that should aid in understanding the role of GTH cells in the reproduction of the grunting toadfish. This study provided the first neurobiological evidence for further plans in aquaculture.